1961
DOI: 10.1021/j100905a028
|View full text |Cite
|
Sign up to set email alerts
|

THE VARIATION OF LATTICE PARAMETER WITH CARBON CONTENT OF TANTALUM CARBIDE1

Abstract: A lattice constant of a. = 4.4555 =t 0.0003 A. has been determined for TaCo.ast * 0.00'1 at 25". The equation a 0 = 4.3007 + Solution of this equation for TaCl.oo 0.1563 (C/Ta) has been calculated relating composition to lattice parameter of TaC.gives a lattice parameter of 4.4570 =k 0.0010 A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

1962
1962
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(68 citation statements)
references
References 0 publications
4
64
0
Order By: Relevance
“…Using similar crystal growth conditions, Robins determined values of the lattice parameter between 4.4550 and 4.4555 A, the composition of the crystals being determined as TaC0.96. According to the data of Bowman [21], a lattice parameter of 4.456 A corresponds to a composition TaC0.99. Electron microprobe analysis showed that the bulk of each crystal contained only tantalum and carbon but in some crystals one or two small inclusions of iron and carbon were present.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using similar crystal growth conditions, Robins determined values of the lattice parameter between 4.4550 and 4.4555 A, the composition of the crystals being determined as TaC0.96. According to the data of Bowman [21], a lattice parameter of 4.456 A corresponds to a composition TaC0.99. Electron microprobe analysis showed that the bulk of each crystal contained only tantalum and carbon but in some crystals one or two small inclusions of iron and carbon were present.…”
Section: Methodsmentioning
confidence: 99%
“…The calculated lattice parameters were plotted against the Taylor-Sinclair function, 89 + cos20/0), and extrapolated to 0 = 0 ~ The corrected lattice parameter was 4.430 4-0.002 A. This corresponds to a composition TaC0.83+0.01 using the data of Bowman [21].…”
Section: Decarburised Crystalsmentioning
confidence: 99%
“…This broad range of composition of the carbide phase will reflect itself in a change of certain physical properties of the carbide, as C vacancies will act as powerful scattering centers for electrons and phonons. Within the range, there will be a variation of several properties: the lattice parameters and density, 35 Hall coefficient, 36 transition temperature to the superconducting state, 37 coefficient of thermal expansion, magnetic susceptibility, heat of formation, and ͑technologically important for microelectronics͒ the resistivity. 10 It is clear that one has to take this into account, when searching for reliable contacts for semiconductors.…”
Section: Discussionmentioning
confidence: 99%
“…The matrix y is a NaCl structure with a lattice parameter, at the solubility limit, of 4.4104 A. 10 T h e arrangement of a unit cell of this structure is shown in Figure 2 (not taking into account vacant carbon sites). Any (111) plane of this structure may be considered to consist entirely of carbon or tantalum atoms in a hexagonal arrangement with a spacing of 3.12 A between nearest neighbors.…”
Section: Modelmentioning
confidence: 99%